Desain didaktis berbasis Permainan Tradisional Engklek di Sekolah Dasar - Revina Putri Hermawan Rerev (Paedagogia: Jurnal Pendidikan, 2021)
Abstract This research motivated by the findings of learning obstacles experienced students in material around square. This is known based on the results of test questions conducted during preliminary study to fourth grade elementary school students. To overcome learning obstacles experienced by students, researchers will design a didactic design. The purpose of this study is to describe the didactic design on the material around square and describe the students' responses the implementation of didactic design. The didactic design can be interpreted learning design that emphasizes the didactic aspect, namely the teacher's teaching method. This study uses method with a Didactical Design Research (DDR) research design consisting of three research stages, namely a prospective analysis of the didactic situation before learning (prospective analysis) in the form of a Hypothetical Didactic Design including ADP (Pedagogical Didactic Analysis), metapedadidactive analysis, and retrospective analysis (retrospective analysis), with data collection techniques used in the form of interviews, observations, and attitude scales. The research subjects were 26 students in grades IV and VI and 1 teacher for grade IV at SDN 1 Sindangrasa. Based on results of study, through application of the didactic design carried out in stages I and II, can help overcome learning obstacles experienced by students in the material around a square. This is shown from the students' responses on the attitude scale, results of the LAS (Student Activity Sheet) work and interviews with teachers. In addition, didactic design is able to create a fun and meaningful learning atmosphere for students. Keywords: learning obstacle, didactical design research, square, meaningful learning, LAS Abstrak Penelitian ini dilatarbelakangi oleh adanya temuan learning obstacle yang dialami siswa pada materi keliling persegi. Hal ini diketahui berdasarkan hasil soal tes yang dilakukan pada saat studi pendahuluan kepada siswa kelas IV Sekolah Dasar. Untuk mengatasi learning obstacle yang dialami siswa, peneliti akan merancang sebuah desain didaktis. Tujuan dari penelitian ini adalah untuk mendeskripsikan desain didaktis pada materi keliling persegi serta memaparkan respon siswa dan guru terhadap implementasi desain didaktis tersebut. Desain didaktis dapat diartikan sebagai desain pembelajaran yang lebih menekankan pada aspek didaktik yakni cara pengajaran guru. Penelitian ini menggunakan metode Didactical Design Research (DDR) yang terdiri dari tiga tahap penelitian, yakni analisis situasi didaktis sebelum pembelajaran (prospective analysis) berupa Desain Didaktis Hipotesis termasuk ADP (Analisis Didaktis Pedagogis), analisis metapedadidaktif, dan analisis retrospektif (retrospective analysis), dengan teknik pengumpulan data yang digunakan berupa wawancara, observasi, dan skala sikap. Subjek penelitian yaitu 26 siswa kelas IV dan VI serta 1 guru kelas IV SDN 1 Sindangrasa. Berdasarkan hasil penelitian, melalui penerapan desain didaktis yang dilakukan pada tahap I dan II dapat membantu mengatasi learning obstacle yang dialami siswa pada materi keliling persegi. Hal ini ditunjukkan dari respon siswa pada skala sikap, hasil pengerjaan LAS (Lembar Aktivitas Siswa) serta wawancara terhadap guru. Selain itu, desain didaktis mampu menciptakan suasana pembelajaran yang menyenangkan dan bermakna bagi siswa. Kata kunci : hambatan belajar, desain didaktis, persegi, pembelajaran bermakna, LAS